THE ANALYSIS OF MORPHOLOGICAL PROCESS OF STUDENTS’ ENGLISH UTTERANCES - Alhasibunur, Alhasibunur (JOLLT Journal of Languages and Language Teaching, 2018)
The aim of this research is to know the kind of Morphological process that the students mostly use in their utterances. This research was qualitative research and the design was used is Phenomenology design and natural setting. The subject of the study was the fourth semester students who were taking Public Speaking subject in English Department of IKIP Mataram. This subject was limited only to fourth semester students in academic year 2017/ 2018. Object of the research was affixation in English lexical category based on students’ English utterances in Public Speaking class. There were 2 instruments that used; primary instrument and secondary instrument. The main instrument in this research was the researcher. Secondary instrument of this research were recording and note taking. Technique of data collection in research was direct observation with non-controlled observation. The technique of data analysis was descriptive analysis. The results were the kind of Morphological process that the students mostly used was Derivational, which was a major process that frequently showed up. Affixation that mostly used by the students was Suffixation.